Ocena rozwiązań i doświadczeń brytyjskiego systemu ubezpieczeń terrorystycznych - Manikowski, Piotr (Wydawnictwo Akademii Ekonomicznej im. Oskara Langego we Wrocławiu, 2007)
Terrorist attacks are no longer rare events and they evoke real danger. In the recent years it has been done quite a lot to fight against international terrorism, however, spectacular attacks still happen. The most terrible, after the 9/11 events, include attacks in Madrid (11.03.2004) and in London (7.07.2005). Thus, as numerous preventive activities are not fully successful, in the most threatened states also issues connected with financing and insuring the risk of terrorism were solved. The goal of this paper is an assessment and analysis of experience of British system of terrorism insurance in the light of the 7 July 2005 London bombings. (original abstract)
Prace Naukowe Akademii Ekonomicznej we Wrocławiu; 2007; nr 1176, s. 253-259